Hematological and biochemical indices, growth performance, and puberty of goats fed with Mombasa and blue panic as salt-tolerant alternatives to alfalfa under arid conditions - Zaher, Hany Ahmed; Mesalam, Ayman; Al Bloushi, Adel Ibrahim; Tolba, Ameer; Swelum, Ayman A.; Abu-Alrub, Ihsan (Frontiers in Veterinary Science, 2022)
The objective of this study was to evaluate the impacts of Mombasa or Blue Panic as salt tolerant alternatives to Alfalfa on growth performance, puberty, blood haematology, serum metabolites, and serum mineral profile in growing goats. Twenty four growing goats of 4 months old age with 14.45 ± 0.6 kg average body weight were assigned, in a completely randomized design, to three treatment diets with 8 animals per treatment. Weights of each animal were measured at the onset of the trial and subsequently on a weekly basis until the end of the trial duration. A pair of blood samples were collected from each goat, via jugular vein puncture and were subjected to either haematological or biochemical analysis. The results showed that treatment diets had no significant effects (P > 0.05) on final body weight and total body weight gain. However, Blue Panic had significantly increased (P < 0.05) neutral detergent fiber and crude protein digestibility. The diet influenced MCV that was significantly higher (P < 0.05) in the Alfalfa group. The serum concentration of glucose was significantly increased (P < 0.05) in Blue Panic fed group while the urea was increased in Mombasa fed group. Additionally, the serum concentrations of P, Na, and Cl were significantly increased (P < 0.05) in Blue Panic fed group, but Mombasa significantly increased (P < 0.05) the K concentration. In conclusion, the study indicates that Blue Panic ranked the best salt tolerant alternatives to replace Alfalfa resulting in better feed utilization, serum metabolites, and serum minerals with no adverse effects on growth performance and puberty. This study provides new insight into shift to the cultivation of salt-tolerant plants with a high level of crude protein in arid areas is a potential approach for the sustainability of the livestock industry.